Building inter-firm collaboration -Evidence from Vietnamese SMEs in Tourism sector - Phuc Nguyen, Nguyen (Archives of Business Research, 2016)
Inter-firm cooperation has received attention in recent year due to its benefit. However, little has been studied about the way to develop this relationship. In this paper we provide evidence on the development of small and medium-sized enterprises (SMEs) in Vietnam relying on inter-firm relationship. Using a recent national survey in 2014 for tourism sector, empirical results indicate that trust in partner, along with motivation from relationship, are the main predictor of this relationship. Further, it confirms the positive influence of similarities between partners on inter-firm cooperation. Our empirical results indicate that classical determinants of inter-firm relationship including firm age, firm size, location and the ownership are also important in Vietnam. In addition to the traditional indicators we analyze the effect of government support. Direction from the government contributed significantly to the growth of Vietnamese SMEs by fostering inter-firm cooperation, but the importance of this kind of support may be diminishing as private firms do not seem to benefit from this form of support.